Simultaneous Combination of the CDK4/6 Inhibitor Palbociclib With Regorafenib Induces Enhanced Anti-tumor Effects in Hepatocarcinoma Cell Lines - Digiacomo, Graziana; Fumarola, Claudia; La Monica, Silvia; Bonelli, Mara A.; Cretella, Daniele; Alfieri, Roberta; Cavazzoni, Andrea; Galetti, Maricla; Bertolini, Patrizia; Missale, Gabriele; Petronini, Pier Giorgio (Frontiers in Oncology, 2020)
Advanced hepatocarcinoma (HCC) is an aggressive malignancy with poor prognosis and limited treatment options. Alterations of the cyclin D-CDK4/6-Rb pathway occur frequently in HCC, providing the rationale for its targeting at least in a molecular subset of HCC. In a panel of HCC cell lines, we investigated whether the CDK4/6 inhibitor palbociclib might improve the efficacy of regorafenib, a powerful multi-kinase inhibitor approved as second-line treatment for advanced HCC after sorafenib failure and currently under clinical investigation as first-line therapy in combination with immunotherapy. In Rb-proficient cells, the simultaneous drug combination, but not the sequential schedules, inhibited cell proliferation, either in short or in long-term experiments, and induced cell death more strongly than individual treatments. Moreover, the combination significantly reduced spheroid cell growth and inhibited cell migration/invasion. The superior efficacy of palbociclib plus regorafenib emerged also under hypoxia and was associated with a significant downregulation of CDK4/6-Rb-myc and mTORC1/p70S6K signaling. Moreover, regorafenib suppressed palbociclib-induced expression of cyclin D1 contributing to the cytotoxic effects of the combination. Besides these inhibitory effects on cell viability/proliferation, palbociclib and regorafenib affected the cell energy metabolism. The drugs alone downregulated both basal and hypoxia-induced expression of HIF-1α and GLUT-1 proteins. Also glucose utilization was reduced by single drug treatments, although this effect was dependent on the cell models and on the oxygen availability (normoxia or hypoxia). Moreover, regorafenib alone reduced mitochondrial respiration. The combined treatment impaired both glucose utilization and respiration without enhancing the effects of the single agents. Our findings suggest that palbociclib and regorafenib combination may be a valuable therapeutic approach for treatment of advanced HCC.